Perbandingan Kemampuan Antifungi Minyak Atsiri Cengkeh (Eugenia aromatica) dan Ketoconazole 2% terhadap Candida albicans secara In Vitro - Fitri, Amelia Dwi; ., Emiyati; ., Aparaminta (JAMBI MEDICAL JOURNAL "Jurnal Kedokteran dan Kesehatan", 2014)
ABSTRACT Background: Candida albicans is a normal flora in some mucous membranes in the body that are opportunistic, so that in certain circumstances may be pathogenic. Currently the use of traditional medicine as a tendency of increasing antifungal, one of which is a plant that contains essential oils. One of the plants that contain essential oils and widely used in the community are clove (Eugenia aromatica). This study aims to prove the existence of antifungal activity of the essential oil of clove (Eugenia aromatica) against Candida albicans and compared with antifungal activity of ketoconazole 2%. This study was conducted to determine the ability of clove essential oil against the proliferation of the fungus Candida albicans and compare it with the antifungal activity of ketoconazole 2%. Methods: This study was a laboratory experimental study using in vitro testing. The method used is the dilution liquid to assess the Minimal Inhibitory concentration (MIC) and Minimum Levels Kill Concentration  (MKL) essential oil of cloves to the proliferation of the fungus Candida albicans and compare it with the antifungal activity of ketoconazole 2%. The means used to make several serial dilutions of test material with a concentration of 40%, 20%, 10%, 5%, 2.5%, 1.25%, and 0.625%. This study was performed three times of testing. Ketoconazole  used in this study is ketoconazole 2% Results: Of the three testing times obtained MIC clove essential oils against the proliferation of the fungus Candida albicans is 1.25%. While MKL clove essential oils against the proliferation of the fungus Candida albicans is 1.25%. MIC and MKL ketoconazole of three tests on the proliferation of the fungus Candida albicans is 2% Conclusions: The ability of clove essential oil antifungal concentration of 1.25% in inhibiting the fungus Candida albicans is proportional to the ability of antifungal ketoconazole 2% in inhibiting the fungus Candida albicans. While the ability of clove essential oil concentration of 1.25% in killing the fungus Candida albicans is proportional to the ability of antifungal ketoconazole 2% in inhibiting the fungus Candida albicans   Keywords: Essential oil of clove (Eugenia aromatica) - Candida albicans - ketoconazole 2% - MIC-MKL.